Supporting and Studying Organizational Change for Introducing Welfare Technologies as a Sociomaterial Process - Bruzzone, Silvia; Crevani, Lucia (Frontiers in Psychology, 2022)
Welfare technologies (WT) for older people is a rapidly expanding sector that offers a way to tackle the challenge of an aging population. Despite their promise in terms of advances in care services and financial savings, their use is still limited. Their design and implementation remain problematic, as they require changes in working practices through coordination among a multiplicity of actors. In order to address these challenges, the need for change is often expressed in terms of a lack of working methods appropriate to their scope. This has led to a proliferation of different toolkits, guidelines, models, etc.; however, these methods often imply a linear understanding of an implementation project and thus fail to take into consideration the emergent and situated character of the processes that lead up to the adoption of welfare. The aim of this article is to propose an alternative means of providing support for the introduction of these technologies by initiating a process for organizational change. The term “change” is understood here as something that is produced by practitioners—in collaboration with researchers—and not brought by researchers to practitioners. To this end, using the tradition of intervention research as inspiration, a learning process at the crossroads of different practices and objects was initiated. The center of attention of this article’ is the sociomaterial process by which different communities of practitioners interact on the co-creation of a checklist. This is a new working method in which the focus is not the artifact in itself but how it emerges through successive interactions and iterations among different objects, practitioners and researchers, resulting in a joint sociomaterial process that reconfigures power relations and the work objective associated with WT. In other words, a new working method artifact is developed in a process in which practitioners, researchers and contextual objects interact and become one with each another.